2017
DOI: 10.1177/1750698017709872
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative exploration of memory cuing by personal items in the home

Abstract: We are surrounded by personal items that can trigger memories, such as photos, souvenirs and heirlooms. Also during holidays, we collect items to remind us of the events, but not all bring back memories to the same extent. Therefore, we explored peoples’ responses to personal items related to a holiday, using the home tour interviewing method. In total, 63 accounts of cuing responses from nine home tours were analysed using thematic analysis. This resulted in four types of cuing responses: (a) ‘no-memory’ resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…While we find the affective approach productive in theorising fashion consumption and destabilising a hierarchical subject-object relationship, we argue that memory – situated somewhere between the subject’s conscious self and the material fashion objects – also plays a vital role in mediating the relationship between the two. In other words, how the affects, feelings and emotions attached to fashion and clothing objects – both active and inactive – evoke and are evoked by the consumer’s ongoing reminiscence, reconciliation, and renewal of past memories as well as how the tripartite self-memory-object relationships evolve across time is still underexplored (Brown and Reavey, 2014; Freeman et al, 2016; Odabasi, 2022; Zijlema et al, 2019). In consumption studies, how memory (as an actant) works in associating and framing our sense of self and identity through interacting with certain material objects, in this case fashion and clothing items, deserves in-depth analysis.…”
Section: Fashion Affect and Memorymentioning
confidence: 99%
See 3 more Smart Citations
“…While we find the affective approach productive in theorising fashion consumption and destabilising a hierarchical subject-object relationship, we argue that memory – situated somewhere between the subject’s conscious self and the material fashion objects – also plays a vital role in mediating the relationship between the two. In other words, how the affects, feelings and emotions attached to fashion and clothing objects – both active and inactive – evoke and are evoked by the consumer’s ongoing reminiscence, reconciliation, and renewal of past memories as well as how the tripartite self-memory-object relationships evolve across time is still underexplored (Brown and Reavey, 2014; Freeman et al, 2016; Odabasi, 2022; Zijlema et al, 2019). In consumption studies, how memory (as an actant) works in associating and framing our sense of self and identity through interacting with certain material objects, in this case fashion and clothing items, deserves in-depth analysis.…”
Section: Fashion Affect and Memorymentioning
confidence: 99%
“…These ‘things’ have rubbed up against the human in a memorable way over time, and the process creates traces of past experiences with and held within them, eventually becoming part of a meaningful ‘mnemonic assemblage’ (Freeman et al, 2016: 5). Rather than being stored in the consumer’s mind, these memories have been relocalised into the clothing and accessory items, which function as an ‘external memory cluing’ system (Zijlema et al, 2019: 378). Woodward and Greasley (2017) have shown that looking at wardrobes and music collections as personal assemblages – that include both ‘things at rest’ (Banim and Guy, 2003) and items for daily use – gives a more complete understanding of contemporary consumption.…”
Section: Fashion Affect and Memorymentioning
confidence: 99%
See 2 more Smart Citations
“…Further, they are not the only relevant considerations. For example, looking at a photo can evoke abstract feelings and association without recalling specific events (Zijlema et al, 2019).…”
Section: Reconsidering Cued Recallmentioning
confidence: 99%